"Insubordinate and suspicious theologians' readers". The Archdiocesan Seminary of Rosario in the post-conciliar crisis (Res Gesta, 2020)
This article analyzes the conflict between the clergy and the hierarchy of the Catholic Church in Rosario in the late sixties and that led to the resignation of a third of the presbytery. It focuses on the social actors linked to the San Carlos Borromeo Archdiocesan Seminary located in the town of Capitán Bermúdez. It is based on the results of a survey of materials from the seminary library and on information collected in a set of interviews with contemporary inhabitants of that process in the town of Capitán Bermúdez.
Keywords: II Vatican Council; Archdiocese of Rosario; Seminary San Carlos Borromeo; resigning priests